2004
DOI: 10.1016/j.jtcvs.2003.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Gene delivery to aortocoronary saphenous vein grafts in a large animal model of intimal hyperplasia

Abstract: This study characterizes a clinically relevant canine model of aortocoronary saphenous vein graft intimal hyperplasia. In addition, it demonstrates that adenoviral vectors can be delivered ex vivo to the saphenous vein graft vessel wall at subphysiologic distension pressures. This model may be used in future studies to manipulate molecular targets critical in aortocoronary saphenous vein graft intimal hyperplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 24 publications
0
34
0
Order By: Relevance
“…Following vein harvest, the gene transfer solution is infused into the vein lumen and the graft is typically incubated in buffer at room temperature for 20-30 minutes with a distension pressure of approximately 10 mmHg. Following infection, gentle flushing of the vein with heparinized saline removes the majority of unincorporated viral particles 33,81,82 . This strategy has demonstrated excellent transduction efficiency and safety, however there is some concern that higher distending pressures may worsen IH 83 .…”
Section: Vector Delivery Strategiesmentioning
confidence: 99%
“…Following vein harvest, the gene transfer solution is infused into the vein lumen and the graft is typically incubated in buffer at room temperature for 20-30 minutes with a distension pressure of approximately 10 mmHg. Following infection, gentle flushing of the vein with heparinized saline removes the majority of unincorporated viral particles 33,81,82 . This strategy has demonstrated excellent transduction efficiency and safety, however there is some concern that higher distending pressures may worsen IH 83 .…”
Section: Vector Delivery Strategiesmentioning
confidence: 99%
“…P i and the outer diameter (c) were measured in our ex vivo perfusion experiments. Again using derivations and assumptions as described in our previous report [25], we estimated the inner (a) and interfacial (b) radii for each set of measured P i and c, to yield: (5) and (6) where L is the length of the vein segment, and the subscripts p and u refer a quantity to its pressurized state within the perfusion system and its unpressurized state on the benchtop, respectively. Substituting equation (4),equation (5) and equation (6) into equation (3), and evaluating at the mean arterial pressure and at , we can calculate the mid-wall CWS in the polymer wrapped vein from equation 3.…”
Section: Demonstrative Application: Gradual Imposition Of Cws To Avgsmentioning
confidence: 99%
“…Many attempts have been made to inhibit or counter-act the AVG failure modes of early thrombosis, intimal hyperplasia (IH) and accelerated atherosclerosis, including local delivery of genes [5] and drugs [6], as well as minimization of the compliance mismatch at the anastomoses via external mechanical support [7][8][9][10][11][12]. IH has received the most attention as it accounts for 20% to 40% of all AVG failures within the first 5 years [13].…”
Section: Introductionmentioning
confidence: 99%
“…Among the many vector systems, recombinant adenoviral vectors have the advantage of being produced with adequate titers for in vivo applications and being capable of transducing cardiovascular target cells effectively. 4 However, transduction is often handicapped by the induction of an immunological response in the surrounding tissue and limited by a transient gene expression. 5,6 In contrast to the adenoviral vectors, recombinant adeno-associated viral vectors (AAV), based on the serotype 2, allow long-term transgene expression after in vivo application in various tissues with low immunological responses.…”
mentioning
confidence: 99%
“…7,8 The earliest experimental results demonstrated that recombinant AAV was also a promising vector for cardiovascular gene therapy because effective gene transfer into rat arteries, native jugular canine veins and the mammalian myocardium could be observed. 4,6,9 There are, however, pathophysiological differences between normal veins and veins used as bypasses, thus interest in native vein transduction is limited in cardiac surgery; furthermore, expression beyond 3 weeks is of essential importance for clinical use. 6 Higher blood pressure followed by a higher shear stress leads to unavoidable damage to the endothelium perioperatively and is responsible for the alterations in vein grafts.…”
mentioning
confidence: 99%